Manajemen Penguatan Pendidikan Karakter Pada Sekolah Menengah Atas: Management of Strengthening Character Education in High Schools - Panoyo, Panoyo; Riyanto, Yatim; Handayaningrum, Warih (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to describe and analyze data about the management of strengthening character education in Sidoarjo Regency with a multi-case study at SMAN 1 Krian and SMAN 1 Taman. The management component starts from planning, organizing, imple- menting, monitoring, and evaluating the strengthening of character education at SMAN 1 Krian and SMAN 1 Taman Sidoarjo. The results of research related to the management of character education strengthening in Sidoarjo regency (multi-case studies in SMAN 1 Krian and SMAN 1 Parks) indicate that planning for strengthening character education must meet at least five aspects, namely referring to the vision and mission of the school, conducting assessments to identify potential schools, formulate and determine the val- ues of the main characters to be developed, school programs are arranged together with all school components, as well as teachers make character-based learning tools (RPP).